Immunocytochemistry assay in BHK-21 cell line infected with Porcine Sapelovirus - Kumari, Swati (Cytotechnology, 2019)
The present study describes an immunocytochemistry (ICC) assay with self-raised hyperimmune sera and a Baby Hamster Kidney-21 (BHK-21) cell line infected with Porcine Sapelovirus (PSV). Sapelovivus/IVRI/SPF-c-6/2015 strain Indian PSV was isolated from the porcine IBRS-2 cell line and investigated for growth on non-porcine cell lines. After two passages, PSV was successfully grown in BHK-21 and produced the same cytopathic effects as in IBRS-2 such as shrinking of cytoplasm, rounding of cells and detachment of cells from the surface of flask within 24 h. For raising of hyperimmune sera, PSV was grown in IBRS-2 cell line up to the required volume and purified by ultracentrifugation. With self-raised hyperimmune sera in laboratory rats, ICC was performed in BHK-21 cells infected with PSV. Positive signals consisted of large granular aggregates of virus in the cytoplasm near the nucleus, suggesting that PSV can infect cell lines other than those of porcine origin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10616-019-00315-4) contains supplementary material, which is available to authorized users.